2015
DOI: 10.3350/cmh.2015.21.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with silibinin and either sorafenib or gefitinib enhances their growth-inhibiting effects in hepatocellular carcinoma cells

Abstract: Background/AimsSilibinin, the main component of silymarin, is used as a hepatoprotectant and exhibits anticancer effects against various cancer cells. This study evaluated the effects of a combination of silibinin with either gefitinib or sorafenib on hepatocellular carcinoma (HCC) cells.MethodsSeveral different human HCC cell lines were used to test the growth-inhibiting effects and cell toxicity of silibinin both alone and in combination with either gefitinib or sorafenib. The cell viability and growth inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…A study conducted by Gu and coworkers reported that silibinin in combination with sorafenib/gefitinib inhibits growth of cancerous cell lines, but their work mainly emphasize on the efficacy of silibinin-gefitinib combination. [25]. Our result strengthens the idea that sorafenib in combination with silibinin have synergestic effect on HCC cell line.…”
Section: Discussionsupporting
confidence: 86%
“…A study conducted by Gu and coworkers reported that silibinin in combination with sorafenib/gefitinib inhibits growth of cancerous cell lines, but their work mainly emphasize on the efficacy of silibinin-gefitinib combination. [25]. Our result strengthens the idea that sorafenib in combination with silibinin have synergestic effect on HCC cell line.…”
Section: Discussionsupporting
confidence: 86%
“…Silibinin, a polyphenolic flavonoid component isolated from the fruits or seeds of milk thistle (Silybum marianum), has been clinically used to treat various diseases, and it has been suggested that this reagent exhibited protective effects for patients with liver or heart disease. The inhibitory effects of silibinin against cancer were also indicated (11)(12)(13)(14)(15)(16)(17) in tumors such as breast cancer and head and neck squamous cell carcinomas. Our previous study indicated that silibinin inhibited BCa progression (18), leading us to hypothesize a link between silibinin and BCa chemoresistance.…”
Section: Introductionmentioning
confidence: 97%
“…Further, silibinin induced autophagy in human fibrosarcoma HT1080 cells by activation of the p53 by ROS/p38/JNK pathway [170] in melanoma A375-S2 cells [171] and human colon cancer cells SW480 and SW620 [172]. However, silibinin exerted its anticancer effect via the apoptotic pathway in HCC cells, such as Huh7, HepG2, Huh-BAT, Hep3B, HepG2, PLC/PRF5, SNU387, SNU398, SNU449, SNU475, and SNU761cells, and also exhibited growth-inhibitory activity with either sorafenib or gefitinib via a synergistic manner in the SNU761 cell line [173]. Since silibinin is an effective inducer of autophagy in various cell lines, its role as an autophagy-mediated anti-HCC effect needs to be explored further.…”
Section: Polyphenols As Modulators Of Autophagy In Cancermentioning
confidence: 99%